The effect of beet leaf (Beta vulgaris) extract on learning and memory after cerebral ischemic reperfusion in rats - Kobra Mirahmadi; Najmeh Asgharzadeh; Zahra Lorigooini; Marzieh Mardani; Zahra Rabiei; Diana Shahrani; Mohamad Shahrani; Mehrdad Shahrani Korrani (Future Natural Products)
Background and aims: Cerebral ischemia causes tissue oxidative damage and leads to cell death. Antioxidants can reduce the adverse effects of ischemia in the brain. This study was conducted to determine the effect of Beta vulgaris hydroalcoholic extract on learning and memory caused by transient cerebral ischemia. Methods: After preparing the herbal extract, the rats were divided into six groups: control, sham, ischemia, and 3 ischemic groups that received the extract. Ischemia was induced by bilateral carotid artery occlusion for 30 minutes. The control, sham, and ischemia groups received normal saline for two weeks. Three treatment groups received 50, 100, and 200 mg/kg B. vulgaris extract. After conducting behavioral tests, the antioxidant capacity and malondialdehyde (MDA) levels of the rat’s serum and brain were measured. Results: The results showed that the hydroalcoholic extract of B. vulgaris leaves increases the antioxidant capacity of serum and brain. It also reduces the amount of MDA in serum and brain. B. vulgaris extract enhances learning and improves motor balance. Conclusion: This study showed that the hydroalcoholic extract of beet leaves firmly protects brain damage caused by cerebral ischemia. The antioxidant property of this extract may explain this effect.